Analysis of the Creative Process of Elementary School Teachers in Tuban Regency in Creating Dance Choreography - Sari, Ayu Titis Rukmana; Wahyudi, Wahyudi; Zaman , Wahid Ibnu (Universitas Nusantara PGRI Kediri, 2025)
This study is about the creative process of elementary school teachers in Tuban Regency in creating dance choreography. The purpose of this study is to determine the creative process of teachers in creating dance choreography that is in accordance with the characteristics of elementary school children. The research methodology used in this study is a qualitative descriptive analysis approach that describes the data accurately, with data collection techniques, namely: interviews, observations, and documentation. The results of this study teachers can create dance choreography by applying elements that must be prepared in the concept of creating dance works, namely movement, dance music, costume makeup and properties.